Concurrent fabry disease and immunoglobulin a nephropathy: a case report - Li-Na Zhou; Shao-Shao Dong; Sheng-Ze Zhang; Li-Wa Huang; Wen Huang (BMC Nephrology, 2023)
Abstract Background Fabry disease (FD) is an X-linked, hereditary dysfunction of glycosphingolipid storage caused by mutations in the GLA gene encoding alpha-galactosidase A enzyme. In rare cases, FD may coexist with immunoglobulin A nephropathy (IgAN). We describe a case of concurrent FD, IgAN, and dilated cardiomyopathy-causing mutations in the TTN and BAG3 genes, which has not been reported previously. Case presentation A 60-year-old female patient was admitted with a one-week history of facial and lower-limb edema, two-year history of left ventricular hypertrophy and sinus bradycardia, and recurring numbness and pain in three lateral digits with bilateral thenar muscle atrophy. Renal biopsy revealed concurrent FD (confirmed via an alpha-galactosidase A enzyme assay, Lyso-GL-3 quantification, and GLA gene sequencing) and IgAN. Heterozygous mutations in the TTN (c.30,484 C > A;p.P10162T) and BAG3 (c.88 A > G;p.I30V) genes were observed. The patient reported that two of her brothers had undergone kidney transplantation; one died suddenly at 60 years of age, and the other required a cardiac pacemaker. The 35-year-old son of the patient was screened for the GLA gene mutation and found to be positive for the same mutation as the patient. The patient was administered oral losartan (50 mg/day). Enzyme replacement therapy was refused due to financial reasons. Her renal and cardiac functions were stable yet worth closely monitoring during follow-up. Conclusion The family history of patients with concurrent heart and renal diseases should be assessed in detail. Genetic testing and histological examinations are essential for diagnosing FD with IgAN.